Workshop Media Pembelajaran Kewirausahaan Bagi Guru SMA dan SMK di Kota Palembang - Nova Pratiwi; Neta Dian Lestari; Diana Widhi Rachmawati; Hendri Gunawan; Januardi Januardi; Chandra Kurniawan; Masnunah Masnunah; Boby Agus Yusmiono (Jurnal Pengabdian Masyarakat (abdira), 2021)
This Community Service activity aims to provide insight to teachers and students about the use of a variety of learning media which is an important skill of a teacher in learning activities in the classroom. This community service is carried out virtually through the Zoom meeting application with the presentation method and open discussion. Participants in this activity were 20 teachers from high schools (SMA) and vocational high schools (SMK) in Palembang City and students of the Accounting education program at PGRI Palembang University. The results of the workshop activities carried out, participants gained insight into the variety of learning media that can be applied to optimize entrepreneurship learning activities in the classroom. Through open discussions, participants had the opportunity to share their views on the paradigm shift in education thanks to the development of information technology that accelerates the flow of knowledge, as well as how to optimize the quality of learning by utilizing information technology.